2013
DOI: 10.1111/phpp.12051
|View full text |Cite
|
Sign up to set email alerts
|

Collagen hydrolysate intake improves the loss of epidermal barrier function and skin elasticity induced by UVB irradiation in hairless mice

Abstract: Collagen hydrolysate administration affects epidermal barrier function and dermal skin elasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 29 publications
4
44
0
1
Order By: Relevance
“…On the other hand, several reports have shown that treatment with CP ingestion only significantly improves epidermal thickening and impairment of skin elasticity in UVB-irradiated hairless mice. [26][27][28] These data indicate that treatment with CP only discriminates rescue effects between hairless Sod1 −/− and UVB-irradiated hairless wild-type mice. In fact, Sod1 −/− fibroblasts exhibit marked loss of cell viability and a significant increase in apoptotic cell death associated with a 10-fold increase in intracellular reactive oxygen species (ROS) generation.…”
Section: Discussionmentioning
confidence: 78%
“…On the other hand, several reports have shown that treatment with CP ingestion only significantly improves epidermal thickening and impairment of skin elasticity in UVB-irradiated hairless mice. [26][27][28] These data indicate that treatment with CP only discriminates rescue effects between hairless Sod1 −/− and UVB-irradiated hairless wild-type mice. In fact, Sod1 −/− fibroblasts exhibit marked loss of cell viability and a significant increase in apoptotic cell death associated with a 10-fold increase in intracellular reactive oxygen species (ROS) generation.…”
Section: Discussionmentioning
confidence: 78%
“…Fish scale collagen hydrolysate was purchased from Nitta Gelatin (Osaka, Japan). This amount of collagen hydrolysate is approximately equivalent to oral ingestion of 2.0 g collagen hydrolysate/kg body wt/day (32). The composition of the experimental diets is shown in Table 1.…”
Section: Experiments 1 (Skin Evaluation In An Aging Mouse Model)mentioning
confidence: 99%
“…Stratum corneum water content and skin elasticity were assessed under standardized conditions (external temperature 24 Ϯ 1°C and humidity 50 Ϯ 10%). Stratum corneum water content and skin elasticity were measured with a SKICON 200-EX skin surface hygrometer (I.B.S., Shizuoka, Japan) and a Cutometer SEM575 (Courage and Khazaka Electronic, Cologne, Germany), as described previously (32). The kinetics of skin displacement (2 mm diameter probe) was measured over a 2 s interval in response to a 300 mbar suction, followed by a 2 s relaxation period after termination of the suction.…”
Section: Experiments 1 (Skin Evaluation In An Aging Mouse Model)mentioning
confidence: 99%
See 1 more Smart Citation
“…6) Collagen hydrolysate (CH) also improves the skin moisture content 7) and skin elasticity. 8) In this study, we describe the pharmacological effects of a dietary herb extract (HE) from E. ulmoides leaves and Korean ginseng, and a combination of HE and CH, on hairless mouse skin under repeated UV irradiation.…”
mentioning
confidence: 99%